1986
DOI: 10.1097/00000658-198611000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Branched Chain Amino Acid Uptake and Muscle Free Amino Acid Concentrations Predict Postoperative Muscle Nitrogen Balance

Abstract: Amino acid solutions rich in branched chain amino acids (BCAA) are commonly utilized both clinically and in experimental protocols in an attempt to reduce skeletal muscle and whole body protein catabolism. To investigate the effectiveness of BCAA infusion, amino acid formulas containing varying concentrations of BCAA were given during operation in this study to three groups of dogs undergoing a standard laparotomy and retroperitoneal dissection. A fourth group was given saline alone. With the use of previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Arginine has immunomodulatory effects, promotes wound healing and protein synthesis, and is a precursor for nitric oxide 12 . BCAA promote protein transcription and translation and inhibit protein degradation 13–15 . Altered circulating or tissue concentrations of these specific amino acids have been found in various disease states 3,14,16,17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine has immunomodulatory effects, promotes wound healing and protein synthesis, and is a precursor for nitric oxide 12 . BCAA promote protein transcription and translation and inhibit protein degradation 13–15 . Altered circulating or tissue concentrations of these specific amino acids have been found in various disease states 3,14,16,17 .…”
mentioning
confidence: 99%
“…BCAA promote protein transcription and translation and inhibit protein degradation 13–15 . Altered circulating or tissue concentrations of these specific amino acids have been found in various disease states 3,14,16,17 . Alterations in BCAA often have been assessed by comparing the ratio of BCAA to aromatic amino acids (AAA) (ie, phenylalanine and tyrosine) or by the Fischer ratio, which is the molar ratio of BCAA : AAA 18,19 …”
mentioning
confidence: 99%
“…Results from our laboratory (34,35) and from other investigators (23,29) have shown that hemodialysis (HD) induces muscle protein catabolism. BCAA and glutamine have been shown to have a regulatory effect on protein turnover (25,32). Despite their qualitative and quantitative importance, the kinetics of alanine and glutamine in ESRD are largely unknown.…”
mentioning
confidence: 99%
“…In both stressed and normal animal and human models, the infusion of BCAA has been found to increase the release of glutamine from skeletal muscle and to elevate the plasma glutamine concentration. 5,7,25–27 Johnson et al 28 studied the effect of infusing BCAA‐enriched parenteral nutrition (i.e. 45% of amino acids compared with the 6–18% found in conventional parenteral nutrition) on protein and glutamine kinetics in dogs after laparotomy.…”
Section: Metabolismmentioning
confidence: 99%